2014
DOI: 10.14319/ijcto.0203.5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trends and outcomes of male breast cancer: Experience of a tertiary oncology centre in India

Abstract: Purpose: Because of its rarity in any oncology centre, the clinical trends of male breast cancer specific to its geographical distribution have remained relatively unexplored. This study was done to analyze the clinico-pathological data, treatment given and survival patterns of male breast cancer patients visiting our tertiary medical centre and compare our results with available literature. Methods: All male breast cancer patients registered at our clinic from 2003 to 2009 were included. Frequency distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
4
7
0
Order By: Relevance
“…[ 1 2 ] We have summarized the data on available Indian series on male breast cancer [ Table 3 ]. [ 4 5 6 7 8 9 10 11 ] Clinical and demographic finding are in concordance with the reported Indian series. Most studies show that male breast cancer presents in an advanced stage while most of our patients were in early stage.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[ 1 2 ] We have summarized the data on available Indian series on male breast cancer [ Table 3 ]. [ 4 5 6 7 8 9 10 11 ] Clinical and demographic finding are in concordance with the reported Indian series. Most studies show that male breast cancer presents in an advanced stage while most of our patients were in early stage.…”
Section: Discussionsupporting
confidence: 88%
“…[ 3 ] Literature pertaining to male breast cancer is sparse, particularly in our country. [ 4 5 6 7 8 9 10 11 ] The present study was done with an aim to analyze the clinicopathological and survival characteristics of male breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies show nipple involvement as an early event in a significant number of male patients. 12,13,23 This is in concordance with our findings.…”
Section: Clinical Presentationsupporting
confidence: 93%
“…18 The median age of MBC in Indian studies is 5-10 years younger than that reported in western literature. [8][9][10][11][12][13][14][15][16][17] In our study, also the median age was 58 years with an age range of 36-76 years. This is almost a decade earlier than what is being reported in the West.…”
Section: Agementioning
confidence: 91%
See 1 more Smart Citation